2019
DOI: 10.1049/mnl.2018.5806
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and improvement of PCL/alginate/PAAm scaffold via selective laser sintering for tissue engineering

Abstract: In this work, porous polycaprolactone (PCL) scaffolds were designed and fabricated using selective laser sintering (SLS). The critical processing parameters of the SLS for PCL were optimised. This work post-processed these PCL scaffolds to produce PCL/alginate/ polyacrylamide (PAAm) scaffolds to improve their performance. The experiment mechanical property assessment showed that the sample's average elastic modulus increases from 6.99 MPa (PCL) to 12.67 MPa (PCL/alginate/PAAm), and the elongation at break of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…[60] Wu et al prepared PCL scaffold using SLS, and found that the scaffold exhibited great porosity, mechanical properties and biocompatibility. [208] By using this method, the micropore system including the size, shape, distribution, spatial orientation, and connectivity in bone scaffold can be accurately controlled by matching the laser spot diameter and scanning spacing, thus meeting the spatial structure requirements of bone regeneration. Meanwhile, any complex shape and individual characteristics of bone scaffold can be quickly prepared according to the different shapes of bone defect.…”
Section: Individual Shapementioning
confidence: 99%
“…[60] Wu et al prepared PCL scaffold using SLS, and found that the scaffold exhibited great porosity, mechanical properties and biocompatibility. [208] By using this method, the micropore system including the size, shape, distribution, spatial orientation, and connectivity in bone scaffold can be accurately controlled by matching the laser spot diameter and scanning spacing, thus meeting the spatial structure requirements of bone regeneration. Meanwhile, any complex shape and individual characteristics of bone scaffold can be quickly prepared according to the different shapes of bone defect.…”
Section: Individual Shapementioning
confidence: 99%
“…Moreover, this method can use ultra-high molecular weights of polyethylene. Unfortunately, in this process, an additional procedure is required to remove the injected powder, which, in addition to its high operating temperature, is the main disadvantage of SLS [ 5 , 141 ]. In addition to RP, relevant methods include stereolithography (SLA) [ 142 , 143 , 144 ] and fused deposition modeling (FDM) for creating an object through the controlled deposition of molten material [ 5 , 145 , 146 ].…”
Section: Scaffold For Articular Cartilage Repair: Requirements Mamentioning
confidence: 99%
“…Alginate is a naturally occurring anionic polymer typically obtained from brown seaweed, which is used as a core, giving stability in MCs due to its biocompatibility, low toxicity, low cost, and fast sol–gel transition in contact with divalent cations. However, this polymer is unable to specifically interact with mammalian cells due to the presence of negative charges and its deficiency of integrin domains [71–73]. Thus, conventional methods to overcome this disadvantage include blending with natural proteins such as silk proteins.…”
Section: Silk Fibroin‐based Mcsmentioning
confidence: 99%
“…Although the use of bioreactors to perform cell seeding on MCs is a promising way to mimic and simulate the biological environment in order to obtain 3D constructs, studies of fibroin‐based MCs with dynamic cell culture are still scarce [60–74].…”
Section: Future Perspectivesmentioning
confidence: 99%